O problema da dedução na filosofia moral kantiana - Rissi, João Paulo (2022)
The subsection IV of section III of Kant’s Groundwork of the metaphysics of morals formulates the question, "how is a categorical imperative possible?" For this question to be answered the Groundwork requires a proof of the actual possibility of the supreme principle of morality under human conditions. The question then focuses on the legitimacy of using a principle of pure practical reason, that is: to submit the categorical imperative to transcendental deduction. In the Critique of Practical Reason, Kant dispenses with a deduction and states that the task of asking about the possibility of the moral law is vain, since it is presented as a Faktum der Vernunft that would legitimize, by itself, the human will. Therefore, what was previously, in GMS, indispensable: (to prove the legitimacy of the pure use of an a priori practical principle), ceases to be so in the KpV, with the introduction of an a priori fact that would be the consciousness of the moral law. The introduction of the concept of Faktum der Vernunft was criticized by some interpreters and philosophers. Schopenhauer, for example, accuses Kant of having turned the categorical imperative into a "hyperphysical fact within the mind." Such objections, which see irreconcilable positions or tension between the GMS and the KpV fail to take into account that Kant's goals are distinct in each of the works with regard to reflection on morality: the supreme principle of morality (which needed a deduction of its legitimacy that would prove that morality is not an illusion, in the GMS) is not left behind by a Faktum inherent in human reason, as can be found in the KpV. Awareness of the moral law is a Faktum of reason, and the categorical imperative is the supreme principle of morality. Distinct things. It requires, in order to think the Kantian reflection on morality in two distinct moments, to investigate the following points: (i) how the deduction of the categorical imperative is developed in section III of the GMS and its implications; (ii) what is the Faktum der Vernunft and why a deduction of the moral law would not only be dispensable, but it would not even make sense to expect there to be one in the KpV, since the GMS had already settled the question about the possible synthetic use of pure practical reason; (iii) Kant does not ask about a deduction of the moral law, but only of the categorical imperative. These points contribute to support the thesis we defend here: to show that, although a deduction exists only in GMS, the moral law, which is secured through a Faktum, is, under human circumstances, the categorical imperative itself. This means that even if the human being is conscious, a priori, of the moral law, he must also want to act morally: hence the moral obligation provided only by a categorical imperative comes in.